Determinants of inflation differentials in the euro area: Is the New Keynesian Phillips Curve enough? - Lagoa, S. (2012)
In the euro area, inflation rates diverged after the creation of the single currency, and started to converge again after mid 2002. Against this background, this paper studies the determinants of inflation differentials in the euro area. We start by using the New Keynesian Phillips Curve (NKPC) to explain inflation differences for a panel of countries. It is found that expected inflation and exchange rate movements are important in causing diverging inflation dynamics, while lagged inflation and exchange rates dynamics are not. Moreover, the Incomplete Competition Model (ICM) adds explanatory power to the NKPC in describing inflation dynamics across countries. Not only the former model is not encompassed by the latter, but also the variables proposed by the ICM turn out as significant: the growth of nominal Unit Labour Cost and the long-run disequilibrium between prices and costs explain inflation differentials.